Predominance of English cotton fabrics in Tunisia and Morocco in the context of the Protectorate 1912-1922 - ELLOUMI, Ali; Abdelmajid, DJEMEL (Advances in Social Sciences Research Journal, 2021)
According to French and British sources, the English cotton fabrics, dominated in many years in the French protectorate, in Tunisia and Morocco, mainly between 1912-1922.This situation can be explained by several factors, Such us the continuity of capitulation régime for many years, after the fall of Tunisia and Morocco under the French dominance.